Table of Content - - (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content:1. The extent to which the Kitab al-Tawhid 2 course for the second year of secondary school  includes the standards of the Education and Training Evaluation CommissionMr. Abdul-Mohsen Abdullah Al-Harbi ,Prof. Fahd Abdul-Aziz Abanmi2. The Effect of Using Dual Situated Learning Model (DSLM) to Teach Chemistry in the Development of Conceptual Comprehension of Secondary School Female StudentsMs. Ebtisam Ali Hamdi3. The effect of using the learning-by-play strategy on female students’ achievement in chemistry and their attitudes towards subjectMs. Nadia Obidullah Abu Zaherah ,Eman Khaled Al-Harbi , Lara Ali Al-Shehri4. The role of the teacher in developing awareness of environmental risks among primary school students in Makkah Al-Mukarramah in light of the cognitive learning theoryMr. Mukhlid Saad Alotaibi5. The Degree of Islamic Studies Teachers' Use of Constructivist Theory Principles in Teaching SituationsMr. Ali Atiyah Ali Al-Malki6. The level of systemic thinking skills (perceiving relationships and structure) in mathematics among female primary school students in Al-Makhwah GovernorateMs. Mona Sultan Musleh Al-Bogami ,Prof. Abdul-Malik Misfer Al-Maliki ,Asst-Prof. Sultan Safar Al-Maliki7. The effectiveness of using augmented reality technology in raising the on learning mathematics  among students with learning difficulties in the third grade of primary school in Makkah Al-MukarramahCo-Prof. Hanan Ali Bagabas, Ms. Lina Nayef Asiri
Keywords: Journal of Curriculum and Teaching Methodology